The Best Advice I Ever Got - The Business Today Team (Collins Business, 2010)
The Best Advice I Ever Got is a treasure trove of advice that worked for the who s who of India s corporate world and its opinion makers. Featured here are insightful pieces of advice collected over a lifetime by personalities such as A. P. J. Abdul Kalam, Azim Premji, Aamir Khan, Shahrukh Khan, Javed Akhtar, R. C. Bhargava, Kiran Mazumdar-Shaw, Dr Devi Shetty, Rama Prasad Goenka, Prasoon Joshi, Harsh Mariwala and Karan Johar The range of experiences dealt with covers everything fromnimproving relationships to business skills. For a reader looking forninspiration or simply some practical advice, this is a book wellnbought.